Halal Assurance System (HAS) 23000 Perspective George Robert Terry - Purwanto, Hery; Rofiq, Ahmad; Mashudi, Mashudi (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2020)
The company's success in achieving the goals that have been set is due to having good managerial skills in planning, organizing, mobilizing, and controlling. Many companies are then looking for a system model that can lead to the achievement of goals. If the model or system is considered capable of leading to the achievement of organizational goals then the system is considered an Expert System. One of them is the Halal Assurance System (HAS 23000), which is a management system used as a model by companies in implementing halal production processes. The HAS23000 concept certainly has a management construction that includes functions in management. This research is library research using a qualitative descriptive analysis approach. The results of the study show that the 11 criteria in HAS23000 are divided into management functions in the perspective of George Robert Terry, namely criteria 1 is a planning function, criteria 2 is an organizing function, criteria 3 is a function of movement, criteria 4, 5, and 6 covers all management functions. That is planning, organizing, mobilizing, and controlling, and finally, the criteria 7, 8, 9, 10, and 11 are the function of control or supervision. With the theoretical approach of George Robert Terry's management function in analyzing the management functions contained in HAS 23000, this is the novelty of previous researchers.